Necroptotic neuronal cell death in amyotrophic lateral sclerosis: A relevant hypothesis with potential therapeutic implication?. (November 2020) - Chevin, Mathilde; Sébire, Guillaume; Deltenre, Paul; Kadhim, Hazim
Abstract: Necroptosis is emerging among possible mechanisms underlying cell death in neurodegenerative diseases. In this line, we hypothesize that necroptosis might be implicated in neuronal cell death in amyotrophic lateral sclerosis (ALS). To support this hypothesis, we hereby provide pilot data as well as some findings from the literature about the expression of key markers of the necroptotic pathway in ALS. Our preliminary data indicate the upregulation of key markers of necroptosis activation in lower motor neurons of the spinal cord. These human-derived data combined with some clinical and preclinical findings support our hypothesis testing the involvement of necroptosis in lower motor neurons death in ALS patients. These results pave the way to deepen the role of necroptosis in ALS using both preclinical and clinical approaches. If confirmed, this hypothesis might raise new interventional strategies to alleviate neurodegenerative process in ALS.